How Linux works : what every superuser should know - Ward, Brian, 1972- (No Starch Press, 2021)
Provides updated information on the inner workings of the Linux operating system, including how the kernel manages devices, device drivers, and processes how networking, interfaces, firewalls, and servers work and how to write effective shell scripts.